PUSHING THE BOUNDARIES. - KIRKPATRICK, JACQUELINE (Creative Nonfiction)
The article presents news brief on various topics. On September 7, 1996, rapper Tupac Shakur was shot in a drive-by and the shooter has never been identified. The first known sightings of the hacker group started in 2003 and it has been credited with attacking hate groups. Common soldiers in the British Army are named Tommy Atkins.